Parents and GPs' understandings and beliefs about food allergy testing in children with eczema: qualitative interview study within the Trial of Eczema allergy Screening Tests (TEST) feasibility trial. Issue 11 (18th November 2020) - Clement, Clare; Ridd, Matthew J; Roberts, Kirsty; Santer, Miriam; Boyle, Robert; Muller, Ingrid; Gilbertson, Anna; Angier, Elizabeth; Selman, Lucy; Shaw, Alison R G
Abstract : Aim: To explore parent and general practitioner (GP) understanding and beliefs about food allergy testing for children with eczema. Design and setting: Qualitative interview study in UK primary care within the Trial of Eczema allergy Screening Tests feasibility trial. Participants: Semi-structured interviews with parents of children with eczema taking part in the feasibility study and GPs at practices hosting the study. Results: 21 parents and 11 GPs were interviewed. Parents discussed a range of potential causes for eczema, including a role for food allergy. They believed allergy testing to be beneficial as it could potentially identify a cure or help reduce symptoms and they found negative tests reassuring, suggesting to them that no dietary changes were needed. GPs reported limited experience and uncertainty regarding food allergy in children with eczema. While some GPs believed referral for allergy testing could be appropriate, most were unclear about its utility. They thought it should be reserved for children with severe eczema or complex problems but wanted more information to advise parents and help guide decision making. Conclusions: Parents' motivations for allergy testing are driven by the desire to improve their child's condition and exclude food allergy as a possible cause of symptoms. GPs are uncertain about the role of allergy testing and want more information about its usefulness to support parents and help inform decision making. Trial registration number: ISRCTN15397185 .